(untitled) (Journal of Applied Learning and Teaching, 2024)
Simulation has been widely adopted in medical education. Traditionally, the design of simulation activities was through a hierarchical approach where experts within a speciality contributed to the development of content and assessment processes. Whilst this has proved to be a somewhat reliable method, the effectiveness from the perspective of medical students has rarely been examined. The Ward Simulation Exercise was delivered in the final year of the undergraduate medical curriculum at the University of Dundee. It was designed to assess the capabilities of medical students to prioritise competing demands and work collaboratively within a simulated environment. Medical students were observed by two assessors (normally consultants), who determined whether the student had met the required standard to pass this assessment. This study examined whether the Ward Simulation Exercise enhanced or inhibited the development of medical students’ self-knowledge. This study presented a longitudinal analysis over five years which examined the effect that the Ward Simulation Exercise had on the development of students’ self-knowledge. Medical professionals arguably need to be more inclusive of students in designing simulation activities and the associated assessment process. This could allow students to develop self-knowledge appropriate to their stage of professional development.